TANGGUNG JAWAB NEGARA TERHADAP PEMENUHAN HAK YANG DIMILIKI LANJUT USIA (LANSIA) DITINJAU DARI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 13 TAHUN 1998 TENTANG KESEJAHTERAAN LANJUT USIA (LANSIA) DALAM PERSPEKTIF HAK ASASI MANUSIA - Putri, Clara Izati; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Increasing the number of elderly population (60 years and over) every year continues to increase. This condition causes many elderly people who experience social violence and violations of the rights of the elderly. One form of human rights violations possessed by the elderly is neglect by families, people around or the community who no longer pay attention to the elderly. This should receive special attention from the government in order to realize the welfare of the elderly as expected in Law No. 13 of 1998 concerning Elderly Welfare by providing social protection for the elderly. Social protection is a human right that is owned by every citizen. The government in particular has formulated various regulations aimed at the welfare of its people in Act Number 11 of 2009 concerning Social Welfare. But the fact is, until now there has not been formed a special role from the government in helping neglected elderly get their social welfare, so it can be said that legal protection for neglected elderly people in Indonesia is still vague. This type of research can be classified in normative juridical research, because this research is carried out by examining secondary data and approaches to the law, this normative study examines applicable regulations and relates to the human rights of the elderly. Source of data used are primary data, secondary data, tertiary data, data collection techniques in this study are normative juridical, the data used is literature studyThe results of the study conducted by the author are the role of government or society in realizing the welfare of the elderly is still very weak. This is evidenced by the increasing number of neglect of the elderly themselves. Therefore, to realize the welfare of the elderly as expected by the welfare state (walfare state), the government must take concrete actions in fulfilling the elderly rights that have been regulated in Law No. 13 of 1998 concerning elderly welfare. In an effort to provide protection and fulfillment of the right to the elderly, the government must work extra. One of them is by updating the law governing the elderly so that it can be applied in modern times.Keywords: elderly, neglect of elderly, violation of elderly rights.